SIMULASI ALAT PENDETEKSI LEVEL AIR BERBASIS MIKROKONTROLER ATMEL89S52 - Zulkifli Zulkifli (UNIVERSITAS INDO GLOBAL MANDIRI)
The existence of clean water to meet the needs of very important in all activities. In each day of at least ± 100 liters / day of clean water to meet demand. To meet the needs of clean water that is large enough that a common thing to do is to build the Tower of water. In the daily reality of controlling the water tower are still common negligence in controlling the filling of water into the tower. Besides, it was also a delay in the turn on the motor for recharging water into the tower could affect the emptying of the water tower. Water tower placement also creates new problems. Because in reality, the water tower is always placed on higher ground than the ground, which would complicate the process of monitoring the water level in the water tower. With the advantage of technological developments, researchers will try to create a simulation of the water level detection device based on microcontroller AT89S52. With this tool is expected to be easier to control the availability of water in the water tower.